Access to Financial Services and the Financial Inclusion Agenda around the World : A Cross-Country Analysis with a New Data Set - Ardic, Oya Pinar; Heimann, Maximilien; Mylenko, Nataliya (2012)
Recent empirical evidence highlights that access to basic financial services can make a substantial positive difference in improving poor people's lives. Accordingly, financial sector reforms that promote financial inclusion are increasingly at the core of policymakers agendas. The Consultative Group to Assist the Poor and the World Bank Group, in response, launched the Financial Access project, including a cross-country database on financial inclusion topics and an annual report to inform the policy debate. Using this database, this paper (i) counts the number of unbanked adults around the world at 56 percent, (ii) analyzes the state of access to deposit and loan services as well as the extent of retail networks, and (iii) discusses the state of financial inclusion mandates around the world.